The All-India Muslim League, 1906-1947: A Study of Leadership in the Evolution of a Nation - Becker, Mary Louise (Karachi Oxford University Press, 2013)
In this book, the author takes Pakistan as a case study in a search for better definitions of nations and nationalism, arguing that it exhibits the three essential ingredients for a successful national movement. These are a distinctive integrated community, a particular set of circumstances, and purposeful leadership. She discusses all three elements within the local context, concentrating particularly on the evolving leadership role of the All-India Muslim League as evidenced in contemporary sources. The achievement of Pakistan was primarily the work of Muslim League leaders, and especially of the Quaid-i-Azam, Mohammed Ali Jinnah, but would have been impossible without a prior cohesive community and the stimulus of a neighbouring nationalism.
Include Bibliography, Appendix and Index.
Keywords: All-India Muslim League